The use of Hall effect probes in the detection and sizing of cracks in steel structures - Konefal, T. (Cranfield University, 1991)
The most commonly used method for non-destructive testing (NDT) of welded tubulars in underwater locations is magnetic particle inspection (MPI). This method is effective in terms of crack or defect detection, but requires much diver effort. This work examines the use of Hall effect probes for crack detection and measurement in steel specimens and underwater pipelines and structures. A simple theory of magnetic leakage fields is developed, and how such fields relate to crack characteristics. The finite sizes of the Hall probes employed are taken into account, and an analytic expression for the field from a tapered crack is developed. Practical magnetic signals from a cracked Y-jointed tubular are taken, and shown to be consistent with MPI indications. A double probe system is proposed which enables crack depth measurement to be made irrespective of a knowledge of the crack width or level of magnetisation in the specimen. Experiments using a prototype double probe system show encouraging results on artificial cracks in small specimens, though there is a troubling unknown background bias effect in the measured signals. An instrument using a time differentiated probe signal has been developed which is capable of detecting a crack in a Y-joint at a scan height of up to 5mm with a level of magnetisation rather less than that used by MPI. A method of continuously monitoring a crack in a Y-joint is also described, using multiple differential pairs of probes. The method is found to give indications consistent and comparable with MPI.